On the Matter of Planning the Language Policy for Georgia: The bill “About State Language” initiated by the parliament bureau of Georgia in 2014 - Putkaradze, Tariel (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2014)
There is no whole state strategy towards language policy in Georgia. We think it’s necessary for government to analyze language policy in a whole global context and by summing up the viewpoints of different fields specialists (linguistics, historiography, law, international relations, sociology, psychology) and (not by relying on one group) define state strategy of Georgia towards planning the language and information policies. In case of launching logical/adequate legislation in the field of language policy , government of Georgia will avoid emerging additional risk factors and by implementing balanced language policy will protect both the Georgian state language status (status of Georgian and Abkhazian languages in Abkhazia) and the language rights of ethnical minorities. We think that logical action of government in the nearest future might be denoted in three ways: Until getting back the occupied territories of Georgia and entirely rebuilding control of Georgian government on the whole territory of Georgia, Georgian government should refrain both from enactment of the law “ About the Georgian state language”, and also from ratification of “ European charter for regional or minority languages”; as it’s impossible to implement any regulations about language on the whole territory of Georgia until getting back the occupied territories. If Georgia activates the law “about state language” in resemblance with France, compare: In 1994 they activated the so called Toubon law “about using the French language”, which makes it compulsory to use French language in the following fields: education, business relations, advertisement and trading. Toubon law doesn’t involve reviewing the issue of using regional languages, just it is remarked in point 21 that given law doesn’t restrict legislation about using regional languages, however French government declares that citizens of this country despite ethnical backgrounds represent one nation, the national language for this nation is French language, accordingly the main focus is on protection of state language status. For Georgia “French way” is risky, as citizen consolidation in Georgia doesn’t hold the level which would make the Georgian citizens-ethnical Armenians, Azers, Ossetians, Abkhazians or Russians see themselves as part of Georgian nation; neither ethnical Georgians think that Georgian citizens - ethnical Armenians, Russians, Azers, Ossetians ... are the part of Georgian nation, accordingly French model won’t act peacefully in Georgia: such actions will support neighbor countries plans to activate disintegrated processes in the outskirts of Georgia. Government should define long-term strategy of Georgian state language policy by summing up the viewpoints of field specialists (and not only relying on one group), which will be the basis to activate “the law of Georgia about the state languages, and the languages of authentic and migrant minorities; this law should take into consideration as protecting the Georgian state language status (Georgian and Abkhazian languages in Abkhazia) as Georgian dialects, as the necessity of surviving the varieties of Georgian national language and protecting language rights of ethnical minorities in Georgia. From the presented three directions (protecting state language status, surviving Georgian verbal (domestic) speech and protecting language rights for minorities) protecting language rights for minorities is in better condition; in particular, Georgia recognized the following international legal acts: “ UN declaration on national or ethnical, religion and language minorities”, Oslo recommendation of OSCE Lund Recommendation ... Besides, in 2005 “Framework Convention about National Minorities” was ratified and finally in may 2009 under the signature of prime minister Nika Gilauri “National Conception of Tolerance and Civil Integration and Acting Plan” was published which was worked out on “framework convention” basis and which maximally protects the rights of Armenian, Azer or other language minorities in terms of education and mass media. All in all it’s necessary to make exact qualification of language units existing in Georgia, general language facts and cases as, ambiguity about terms or mistakes become the basis of number of misunderstandings, and more than that - fatal processes